Cechy diagnostyczne jesionu wyniosłego (Fraxinus excelsior L.) z falistością włókien rosnącego na Ukrainie - Sopushynsky, Ivan; Teischinger, Alfred (Leśne Prace Badawcze, 2013)
The paper presents analysis of biometric features of ash with wavy-grained wood, which has decorative appeal. The research results shows that fresh broadleaves ash forest stands growing in the Vinnytsya and Sokyryany Regions of Ukraine have high potential for growing curly ash. The differences between straight-grained and wavy-grained wood density and macrostructure were analysed and estimated. Statistical evaluation of the aesthetic macrostructure of wood characteristics indicated that the length of wave varied from 3.25 to 10.83 mm and its amplitude varied from 0.37 to 1.74 mm. The average width and mean height of anomalies in wood formation were equal to 15.89 mm and 5.00 mm, and their mean occurrence was 30 times m -2 . Average annual growth ring width of wavy-grained ash wood was clearly greater (by 25 %) than that of straight-grained wood. The density of wavy-grained wood was 82 kg·m -3 higher than straight-grained wood after oven-drying and 70 kg·m -3 higher prior to oven-drying.